Structural features of face and neck skin in intraoperative cylinder tension - M. M. Madazimov; M. G. Teshaboev; Z. Q. Raximov (World Scientific Publishing, 2019)
Objective: Recently, significant attention has been paid to the aesthetics of the skin, which has led to the emergence and development, in addition to traditional medical cosmetology, of areas such as aesthetic and plastic skin surgery, surgical cosmetology, and others. Methods: For light microscopy, samples from various sections of the skin of the face and neck (total 57 samples) subjected to stretching, obtained during surgery, were fixed in a 10-12% solution of neutral formalin. After appropriate treatment, the samples were poured into paraffin and 5-7-μm-thick sections were prepared. The general morphology was studied of the sections stained with hematoxylin and eosin. Results: In the spiky layer, the integrity of keratinocyte rows is ensured by numerous desmosomes located at the contacting ends of the processes of neighboring cells. Balloon cell stretching does not lead to disruption of contacts in the forms of interdigitations of the plasma membranes of neighboring cells of the basal layer and ruptures of desmosomes at the ends of processes of neighboring cells of the prickly layer. Conclusion: Intraoperative stretching of the skin does not cause a violation of its general architectonics. In all the studied sections in the epidermis, integrity violations in the form of tears, cracks, etc. are not determined. It was noted with a decrease in the number of rows of cells of the prickly layer. However, no phenomena of acantholysis and cytolysis were noted.